2002
DOI: 10.1074/jbc.m205211200
|View full text |Cite
|
Sign up to set email alerts
|

Upstream of Growth and Differentiation Factor 1 (uog1), a Mammalian Homolog of the Yeast Longevity Assurance Gene 1 (LAG1), RegulatesN-Stearoyl-sphinganine (C18-(Dihydro)ceramide) Synthesis in a Fumonisin B1-independent Manner in Mammalian Cells

Abstract: The longevity assurance gene (LAG1) and its homolog (LAC1) are required for acyl-CoA-dependent synthesis of ceramides containing very long acyl chain (e.g. C26) fatty acids in yeast, and a homolog of LAG1, ASC1, confers resistance in plants to fumonisin B 1 , an inhibitor of ceramide synthesis. To understand further the mechanism of regulation of ceramide synthesis, we now characterize a mammalian homolog of LAG1, upstream of growth and differentiation factor-1 (uog1). cDNA clones of uog1 were obtained from ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
254
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 263 publications
(274 citation statements)
references
References 52 publications
19
254
1
Order By: Relevance
“…For example, LASS1 shows significant preference for C 18:0 fatty acid CoA, whereas LASS5 and LASS6 preferentially catalyze the acylation of (dihydro)sphingosine with myristoyl-, palmitoyl-and stearoyl-CoA rather than very long-chain fatty acid CoAs [31,34]. Initial studies regarding the subcellular localization of LASS family members demonstrate that, in over-expression models of genes, tagged-LASS 1/4/5/6 members were commonly observed to reside at the endoplasmic reticulum [31,32,35]. Dihydroceramides with distinct fatty acyl moieties are then desaturated by dihydroceramide desaturase to form the corresponding ceramides [36].…”
Section: -1 Sphingolipid Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…For example, LASS1 shows significant preference for C 18:0 fatty acid CoA, whereas LASS5 and LASS6 preferentially catalyze the acylation of (dihydro)sphingosine with myristoyl-, palmitoyl-and stearoyl-CoA rather than very long-chain fatty acid CoAs [31,34]. Initial studies regarding the subcellular localization of LASS family members demonstrate that, in over-expression models of genes, tagged-LASS 1/4/5/6 members were commonly observed to reside at the endoplasmic reticulum [31,32,35]. Dihydroceramides with distinct fatty acyl moieties are then desaturated by dihydroceramide desaturase to form the corresponding ceramides [36].…”
Section: -1 Sphingolipid Biosynthesismentioning
confidence: 99%
“…Ceramide synthase activity [71] has been observed in mitochondria-associated membranes where free sphingoid bases are converted to (dihydro)ceramide by (dihydro)ceramide synthases [23]. Moreover, ceramideenriched mitochondria upon treatment with phorbol esters were seen to localize around the nuclear envelope where LASS5 as well as other LASS family members are present [31,32,35]. These spatial changes in subcellular compartments (mitochondria, endoplasmic reticulum, and mitochondria-associated membranes) may play a key role in allowing the accumulation of C 16:0 -ceramide in mitochondria and/or mitochondria-associated membranes.…”
Section: Regulation Of the Salvage Pathway 4-1 The Salvage Pathway Amentioning
confidence: 99%
“…Different length of ceramides were synthesized by different CerS genes [20]. While CerS1 is responsible for synthesis of C18-ceramide [21], CerS2 and CerS4 increase the levels of C24-ceramides and C22-ceramides, respectively [22,23]. C14-ceramides and C16-ceramides were sythesised by CerS5 and CerS6 genes [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key enzymes of the de novo pathway is (dihydro)ceramide synthase, and it has been shown that in Saccharomyces cerevisiae, longevity assurance gene (LAG) members (LAG1p and Lac1p) play a role in the regulation of life span (14) and are also required for ceramide synthase activity (15,16). Recent studies also revealed that one of the mouse homologues of these proteins, known as upstream of growth and differentiation factor 1 (mUOG1 or mouse LASS1) specifically regulates the synthesis of stearoyl (C 18 )-containing sphingolipids, including C 18 -ceramide (17,18). The human homologue of the LAG1 was also identified (named as LASS1; ref.…”
Section: Introductionmentioning
confidence: 99%